The Ethological Study of Glossifungites Ichnofacies in the Modern & Miocene Mahakam Delta, Indonesia - Ery Arifullah (Ikatan Ahli Geologi Indonesia, 2013)
The Glossifungites facies is an ichnofacies which represents an assemblage of burrows that occur in firm, -not lithified- ground. Some geologists believe that the presence of a Glossifungites ichnofacies surface is an evidence of a break between erosion and deposition, which is a boundary of a sequence stratigraphic unit.Although firm ground assemblages are well understood, the Glossifungites ichnofacies concept generates some debates amongst geologists, because firm grounds represent intermediate gradational state between soft ground and hard ground. The level of compaction and dewatering of substrate are varies and controlled by different factors.Arifullah (2005) studied Glossifungites ichnofacies in East Kalimantan, which are common in both modern and Miocene Mahakam Delta system. The identification of Glossifungites ichnofacies in this study is based on ethology and morphological observation of the bioturbations.